The Influence of Store Atmosphere, Store Layout, Point of Purchase Displays, and Promotional Signage on Souvenir Impulse Buying Behaviour - Tahiry, Darwish Khan; Abdillah, Yusri; Mawardi, Mukhammad Kholid (The International Journal of Accounting and Business Society, 2025)
Purpose — There is a notable lack in the comprehensive and integrative understanding of in-store marketing factors, particularly understanding how store atmosphere affects impulse buying collectively in the context of souvenirs in developing countries. The current study fulfils this imbalance by conducting an in-depth investigation into the impact of key in-store marketing variables: store atmosphere, store layout, point of purchase displays, and promotional signage on consumer impulse buying behaviour. Design/methodology/approach — A quantitative data analysis technique is utilised, collecting information through structured questionnaires from domestic tourists purchasing souvenirs at Malang Strudel retail chains in Greater Malang. Smart PLS SEM is used to analyse the interrelationships among variables, based on 99 sample responses collected through purposive sampling. Findings — Results indicate that all four factors —store atmosphere, store layout, point-of-purchase displays, and promotional signage —have a significant positive impact on impulse buying of souvenirs. It showed that pleasant lighting, a hygienic ambience with appropriate music and temperature, easy and convenient placement of merchandise, eye-catching window displays, in-store advertisements, and appealing price-discount signs were effective in triggering spontaneous souvenir purchases among consumers. Practical implications — These outcomes offer valuable insights for retailers and marketers operating in a souvenir shopping context. They can strategically use these in-store stimuli to influence and capitalise on souvenir impulse-buying behaviour, thereby improving sales and the shopping experience. The results offer insights into the dynamics of impulsive souvenir shopping, enhancing knowledge in the context of consumer behaviour and retail management. Originality/value — This contributes to the existing knowledge on impulsive buying behaviour identified in the context of souvenir shops within an emerging economy, with implications that the environment and behavioural factors contribute to consumer decisions in a tourism-driven retail setting.